MENINGKATKAN PRODUKSI ASI MELALUI PEMBERIAN TERAPI SARI TEMULAWAK (curxuma Zhanthorrhiza) PADA IBU MENYUSUI DIWILAYAH KERJA PUSKESMAS SUKORAMBI - Yuningsih (LPPM Universitas dr. Soebandi, 2024)
Background: Breastfeeding is giving Mother's Milk (ASI) to babies. Breast milk is a white liquid produced by the mother's mammary glands through the breastfeeding process. Breast milk is produced in these mammary glands, then the milk enters the milk collecting ducts near the nipples through the milk ducts (ductus), and will be stored temporarily in the shelter until the time comes for the baby to suck it through the nipples. Management using temulawak extract with natural ingredients, will be better and reduce side effects that are harmful to health. The purpose of this study was to find out the increase in milk production in breastfeeding mothers in the working area of the Sukorambi Health Center before and after giving temulawak essence therapy. Method: the method used in this study with the implementation of activities, namely: obtaining a recommendation letter from the university campus of Dr. Soebandi Jember, obtaining a recommendation letter from Bakesbangpol to be given to the Jember District Health Office and then given to the Sukorambi Jember Health Center, obtaining permission from the Sukorambi Health Center to conduct research , identifying problems related to the scope of midwifery, making service strategies related to midwifery problems. The results of the study: it was found that the results of increasing milk production before temulawak extract therapy were 70%, after giving temulawak essence therapy for 7 days routinely (2x a day in the morning and evening) there was an increase in milk production with a percentage of 100%. Based on the experience of increasing milk production in breastfeeding mothers in the working area of the Sukorambi Health Center before and after administration of temulawak extract therapy, it is very effective and it is proven that temulawak can increase milk production in nursing mothers. Conclusion: temulawak extract can increase milk production in breastfeeding mothers in the working area of the Sukorambi Jember Health Center. It is hoped that temulawak extract therapy can be implemented in midwifery care for lactation mothers in the working area of the Sukorambi Jember Health Center.